Advances in dorzolamide hydrochloride delivery: harnessing nanotechnology for enhanced ocular drug delivery in glaucoma management - Sagar R. Pardeshi; Amol D. Gholap; Navnath T. Hatvate; Khushmita D. Gharat; Jitendra B. Naik; Abdelwahab Omri (Discover Nano)
Abstract Dorzolamide hydrochloride (DRZ) is a carbonic anhydrase inhibitor utilized in managing elevated intraocular pressure (IOP) associated with glaucoma. However, its clinical effectiveness is hindered by a short half-life, low residence time, and the need for frequent dosing, highlighting the necessity for innovative delivery systems. This work reviews recent advancements in DRZ delivery, particularly focusing on cyclodextrin complexation and nanotechnology applications. It explores the potential of cyclodextrin derivatives to enhance DRZ’s bioavailability. DRZ cyclodextrin complexes or nanoparticulate systems maintain high drug concentrations in the eye while minimizing irritation and viscosity-related issues. Nanotechnology introduces nanoparticle-based carriers such as polymeric nanoparticles, solid lipid nanoparticles, liposomes, niosomes, and nanoemulsions. These formulations enable sustained drug release, improved corneal permeation, and enhanced patient compliance. Clinical trials have shown that DRZ nanoparticle eye drops and nanoliposome formulations offer efficacy comparable to conventional therapies, with the potential for better tolerability. Overall, this review highlights significant progress in DRZ delivery systems, suggesting their potential to transform glaucoma treatment by addressing current limitations and improving therapeutic outcomes.